2011
DOI: 10.5194/bg-8-41-2011
|View full text |Cite
|
Sign up to set email alerts
|

Annual follow-up of gross diffusive carbon dioxide and methane emissions from a boreal reservoir and two nearby lakes in Québec, Canada

Abstract: Abstract. Surface water pCO 2 and pCH 4 measurements were taken in the boreal zone of Québec, Canada, from summer 2006 to summer 2008 in Eastmain 1 reservoir and two nearby lakes. The goal of this follow-up was to evaluate annual greenhouse gas (GHG) emissions, including spring emissions (N.B. gross emissions for reservoir), through flux calculations using the thin boundary layer model. Our measurements underscored the winter CO 2 accumulation due to ice cover and the importance of a reliable estimate of sprin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 46 publications
3
39
0
Order By: Relevance
“…Under‐ice accumulation of biogenic gases during winter in boreal lakes has been reported to generate significant gas fluxes during the brief period of the spring thaw [ Demarty et al ., ; Kortelainen et al ., ], but this process has rarely been documented in flowing waters [ Dyson et al ., ]. We observed that the average end of winter p CO 2 and p CH 4 were both significantly higher than the ice‐free season concentrations (Figures a and b).…”
Section: Discussionmentioning
confidence: 99%
“…Under‐ice accumulation of biogenic gases during winter in boreal lakes has been reported to generate significant gas fluxes during the brief period of the spring thaw [ Demarty et al ., ; Kortelainen et al ., ], but this process has rarely been documented in flowing waters [ Dyson et al ., ]. We observed that the average end of winter p CO 2 and p CH 4 were both significantly higher than the ice‐free season concentrations (Figures a and b).…”
Section: Discussionmentioning
confidence: 99%
“…The low emissions from open water are similar to those from reservoirs at higher or lower latitudes, but in those cases the littoral zone has not been investigated [29], [30]. Reservoirs differ enormously in the percentage of their area that can be deemed ‘littoral’.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, several studies have compared the amount of CO 2 emitted by these ecosystems to those from natural lakes (see e.g. Tremblay et al ., ; and references therein, Demarty et al ., ) to evaluate their warming potential, among other objectives. However, comparative analyses, in particular cross‐ecosystem comparisons, of lakes and reservoirs with respect to factors driving variation in CO 2 emissions are exceedingly scarce.…”
Section: Introductionmentioning
confidence: 98%